Pengaruh Kualitas Sosialisasi Perpajakan dan Tax Morale terhadap Kepatuhan Wajib Pajak UMKM: (Study pada UMKM Sektor Perdagangan di Kabupaten Dompu) - Firda Rabiatul Ain; Samsudin Samsudin; Dian Urna Fasihat (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of the quality of tax outreach and tax morale on tax compliance among MSME taxpayers in the trade sector in Dompu Regency. Using a quantitative associative approach with simple random sampling, the study sample consisted of 96 respondents, calculated based on the Lemeshow formula. Primary data were collected through a structured questionnaire and analyzed using multiple linear regression techniques with SPSS version 27 software. The test results indicate that, both partially and simultaneously, the quality of tax socialization and tax morale have a positive and significant effect on MSME taxpayer compliance; thus, all hypotheses (H₁, H₂, and H₃) are accepted. The combination of external factors namely communicative education and internal factors namely voluntary moral awareness contributed 45.3% to the variation in taxpayer compliance, while the remaining 54.7% was influenced by other factors outside the research model. These findings confirm that improved compliance among MSME operators in Dompu Regency is optimally achieved when an understanding of regulations resulting from effective outreach is combined with a strong sense of moral responsibility as citizens.